A minimalist self-assembly nanosystem for cancer immunotherapy via multiple immune activation - Weizhe Xu; Shiyuan Wang; Jiayi Zhang; Fang Wang; Zhaogang Sun; Bei Liu; Jun Ye; Hongqian Chu (Journal of Nanobiotechnology)
Abstract In recent years, anti-tumor immunity has emerged as a central focus in cancer research, with the rapid advancement of immunotherapy heralding a new era in cancer treatment. Despite the significant potential of immunotherapy, the use of single-agent approaches or limited combination therapies has not consistently yielded optimal therapeutic outcomes. The strategic and controlled integration of diverse immune activation techniques within a single nanoparticle, utilizing a straightforward and universal methodology, continues to present a substantial challenge. Self-assembly, as a simple synthesis method, offers the possibility of combining multiple therapeutic approaches through straightforward means. In this study, we developed a novel approach to construct a biocompatible nanosystem, named Cu-ICG-CpG-FA (CICF), which was synthesized through one-pot coordination-driven self-assembly of Cu2+ ions, CpG oligonucleotides and indocyanine green (ICG), followed by a surface modification with folic acid. Folic acid, as a ligand, can bind to folic acid receptors expressed on the surface of tumor cells. Cu2+ facilitates chemodynamic therapy (CDT) through the Fenton reaction. ICG serves as a therapeutic for photothermal therapy (PTT) and photodynamic therapy (PDT). Moreover, CDT and PTT/PDT can induce immunogenic cell death (ICD), which is further enhanced by the immune-stimulating effect of CpG, thereby improving the tumor immunosuppressive microenvironment. Therefore, CICF provides a simple and efficient approach to synergistic cancer immunotherapy with promising clinical applications. Graphical Abstract